2021
DOI: 10.3390/jmse9090943
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Recoverable and Reusable Titanium Dioxide Nanocomposite for Water Disinfection

Abstract: A bifunctional magnetic Fe3O4@SiO2@TiO2 or MS-TiO2 antimicrobial nanocomposite was prepared based on simple sol-gel methods with common equipment and chemicals. Reaction pH was found to influence the TiO2 upload in the nanocomposite. The alkaline condition produced the greatest TiO2 upload, while the acidic condition the least. Annealing at 300 °C turned the as-synthesized amorphous TiO2 into one with high content of anatase, the most photoactive form of TiO2. Irradiated by 365 nm UV light, a sample of 30 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Our early studies show that the thin-silica-coated MNP cores were highly stable upon harsh water and heat treatments, which if not coated would oxidize under these highly oxidative environments and become much less magnetically responsive. 16,46 Silica structure may be weakened upon reacting with the moisture in the air. The synthetic conditions employed here, however, were shown to correspond to a very stable silica structure in water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our early studies show that the thin-silica-coated MNP cores were highly stable upon harsh water and heat treatments, which if not coated would oxidize under these highly oxidative environments and become much less magnetically responsive. 16,46 Silica structure may be weakened upon reacting with the moisture in the air. The synthetic conditions employed here, however, were shown to correspond to a very stable silica structure in water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In recent years, advances in nanomaterials have triggered large interest in specifically designed nanocomposite materials for water treatment. The concept of a synergistic combination of two or more nanocomponents into a large one has become a very successful strategy in materials science for achieving highly efficient and specific goals in materials’ property, such as adding new structural and functional properties superior to those of the individual pure components. …”
Section: Introductionmentioning
confidence: 99%
“…Other composites based on TiO 2 have also been proposed as a solution to easily retrieve the photocatalyst powder from the solution to reuse and recycle. Therefore, Keeley et al [87] reported on a sol-gel Fe 2 O 3 -SiO 2 -TiO 2 composite that led to the complete inactivation of E. coli (initial concentration 10 4 CFU/mL) from distilled water under UV light and within 25 min. The photocatalyst was also successful in the disinfection of a real surface water sample containing 500-5000 CFU/mL of different microbes with a 62 ± 3% bacterial count reduction within 30 min.…”
Section: Water Disinfectionmentioning
confidence: 99%